2006
DOI: 10.17705/1cais.01747
|View full text |Cite
|
Sign up to set email alerts
|

Research Models in Information Systems

Abstract: The use of research models in driving scholarly investigation is of great importance in any field, including information systems (IS). As such, a taxonomy of IS research models should be of substantial value to the discipline. Such a taxonomy is developed in this article based on the IS research literature. Eleven model types are examined in detail in order to investigate how they are used by researchers, in articles published in seven leading IS journals during a recent six year period. Interesting results em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The top model type was multi-tier influence diagram. These findings are consistent with the more general rankings found in Palvia et al (2006) as well as the findings in Urbach et al (2009). Multi-tier influence models based on survey data are the dominant paradigm in IT impact studies.…”
Section: Aggregate Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…The top model type was multi-tier influence diagram. These findings are consistent with the more general rankings found in Palvia et al (2006) as well as the findings in Urbach et al (2009). Multi-tier influence models based on survey data are the dominant paradigm in IT impact studies.…”
Section: Aggregate Findingssupporting
confidence: 92%
“…Tables IV and V show the top models and methodologies in descending order. The list of possible models and methodologies came from Palvia et al (2006). The totals are greater than the number of articles because several articles were coded with two models and/or methodologies.…”
Section: Aggregate Findingsmentioning
confidence: 99%
“…Similarly, many studies included additional independent variables that affect KM such as cognitive or economic factors outside the scope of culture and hence are not reported in the analysis. Method type code was based on types of IS research identified in Palvia, Midha, & Pinjani (2006). Sample size, effect sizes, and reliability of measures are necessary for aggregating results for a quantitative meta-analysis (Wu & Lederer, 2009).…”
Section: Coding Processmentioning
confidence: 99%
“…Given that the four propositions corroborate the responses found in the interview transcripts, we derived a prescriptive model, henceforth referred to as the insider threat aggravating variables (ITAV) model. This ITAV model follows a two-tier simple influence diagram that delineates the dependent and independent variables and the relationships among them (Palvia, Midha, & Pinjani, 2006).…”
Section: Discussionmentioning
confidence: 99%